Secondary Prevention of Stroke - MacWalter, R. S. (Thrombosis and Haemostasis, 1999)
Stroke is a common disorder and a leading cause of disability and death. Ischaemia is a more common cause than haemorrhage and radiological imaging is required to accurately differentiate these. Some specific risk factors for stroke are non-modifiable – these include age, gender, racial and hereditary factors. Certain risk factors for ischaemic stroke can be identified and modification of these can be used for secondary prevention – examples include hypertension, heart diseases, atrial fibrillation, diabetes mellitus, dyslipidaemia, smoking, excessive alcohol consumption and carotid stenosis. Carotid endarterectomy is valuable in selected patients. In ischaemic stroke and transient ischaemic attack antithrombotic therapy is an option used in secondary prevention. In atrial fibrillation, warfarin should be used where possible in secondary prevention. When warfarin is contraindicated aspirin should be used. In other patients, an antiplatelet regime is appropriate – aspirin is commonly used and is the least expensive regime. Other antiplatelet agents such as dipyridamole, ticlopidine and clopidogrel may have a place. Younger patients with ischaemic stroke may have a thrombophilia state and should be appropriately investigated.
Keywords: Cerebrovascular disorders; cerebral ischaemia; risk factors; atrial fibrillation; anticoagulants; aspirin; platelet aggregation inhibitors; dipyridamole; ticlopidine; clopidogrel; hypertension